Effectiveness of Structured Diabetes Education Programs in Improving HbA1c and Treatment Adherence Among Newly Diagnosed Patients in Pakistan - Mufti, Khizer Iqbal; Ain, Noor Ul; Nadeem, Namra; Iqbal, Ibtahaj Mohsin; Shaukat, Ibtesam (Biological and Clinical Sciences Research Journal, 2025)
Diabetes mellitus is a major public health challenge in Pakistan, with poor glycemic control and suboptimal treatment adherence contributing to high morbidity. Structured diabetes self-management education (DSME) programs have demonstrated significant benefits globally but remain underutilized in the Pakistani healthcare system. Objective: To evaluate the effectiveness of a structured diabetes education program on HbA1c reduction and treatment adherence among newly diagnosed type 2 diabetes patients in a tertiary care setting in Pakistan. Methods: A quasi-experimental study was conducted at a tertiary care hospital from April to September 2024. A total of 86 newly diagnosed type 2 diabetes patients were divided into two groups: the intervention group received a structured education program (4 sessions over 4 weeks), and the control group received routine care. HbA1c levels and medication adherence (assessed by MMAS-8) were recorded at baseline and 12 weeks post-intervention. Data were analyzed using paired and independent sample t-tests. Results: Participants in the intervention group showed a significant reduction in HbA1c (mean change: –1.6%, p < 0.001) compared to the control group (mean change: –0.3%, p = 0.084). Treatment adherence improved markedly in the intervention group (+2.3 points, p < 0.001) versus minimal change in the control group (+0.5 points, p = 0.067). Patient satisfaction and perceived knowledge also significantly improved in the intervention group (p < 0.001). Conclusion: Structured diabetes education significantly improves glycemic control and medication adherence in newly diagnosed patients. Integration of such programs into routine care is essential to address the diabetes epidemic in Pakistan.